Is a Minimum Wage an Appropriate Instrument for Redistribution? - Aart Gerritsen; Bas Jacobs (Center for Economic Studies and ifo Institute (CESifo), 2014)
We analyze the redistributive (dis)advantages of a minimum wage over income taxation in competitive labor markets. A minimum wage causes more unemployment, but also leads to more skill formation as unemployment is concentrated on low-skilled workers. A simple condition based on three sufficient statistics shows that a minimum wage is desirable if the social welfare gains of more skill formation outweigh the social welfare losses of increased unemployment. Using a highly conservative calibration, a minimum wage decrease is shown to be part of a Pareto-improving policy reform for all countries under consideration, except possibly the United States.
Keywords: D60; H21; H24; J21; J24; J38; 330; minimum wage; optimal redistribution; unemployment; education